THE EFFECT OF ELECTRONIC STORIES AND PUPPET THEATER ON DEVELOPING MATHEMATICAL SKILLS AMONG KINDERGARTEN CHILDREN - Mays Hussein Alzubi, DR. Ibraheem Ali al_naanah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to identify the effect of electronic story and puppet theater on developing mathematical skills among kindergarten children, and the study relied on the quasi-experimental approach, and the study sample consisted of (90) children from the kindergarten divisions in Umm Al-Dinanir Basic Mixed School, they were distributed equally into three groups: the 1st experimental group where studied using the electronic story, and the 2nd experimental group where studied using the puppet theater, and the control group, and the pre-post application of mathematical skills test. The results showed that there were statistically significant differences in each of the skill of counting, the skill of manipulating numbers, the skill of solving problems and the total degree in the post-measurement according to the group variable, and that the differences for each of the counting skill, problem-solving skill and the total degree of the mathematical skills scale in the post-measurement were between the control group and the experimental group using puppet theater in favor of the experimental group, and that the differences in counting skill and the total degree of mathematical skills scale in the post-measurement according to the group variable, were between the experimental group using the electronic story and the experimental group using the puppet theater, in favor of the experimental group using puppet theater. The study recommended the use of electronic stories and puppet theater in teaching mathematical skills because of their clear role in increasing the learning outcome of children.